The influence of physiobiomechanical parameters, technical aspects of shooting, and psychophysiological factors on biathlon performance: A review - Marko S. Laaksonen; Thomas Finkenzeller; Hans-Christer Holmberg; Gerold Sattlecker (Elsevier, 2018)
The biathlon, an Olympic sporting discipline that combines cross-country skiing with rifle marksmanship, entails considerable physiological demands, as well as fine motor control while shooting after intense exercise and under mental pressure. Although much of our knowledge about cross-country skiing is probably also applicable to the biathlon, carrying the rifle and shooting under stress make this discipline somewhat unique. The present review summarizes and examines the scientific literature related to biathlon performance, with a focus on physiological and biomechanical factors and shooting technique, as well as psychophysiological aspects of shooting performance. We conclude with suggestions for future research designed to extend our knowledge about the biathlon, which is presently quite limited. Keywords: Cortical activity, Gaze behavior, Postural balance, Skiing, Triggering